Der "Welsche Gast" des Thomasin von Zerklaere Neue Perspektiven auf eine alte Verhaltenslehre in Text und Bild - Schneider, Christian (Kulturelles Erbe: Materialität - Text - Edition (KEMTE), 2022)
In 1215/1216, Thomasin von Zerklaere composed his Welscher Gast ("The Italian Guest"), the earliest comprehensive book of court etiquette written in German. Up until the Early Modern Age, the work was frequently copied and widely disseminated. Its uniqueness lies not least in the fact that it was, from early on, transmitted together with an extensive cycle of images. This volume brings together studies from Art History, Literary Studies and Musicology into the sources, the didactic concept, the transmission of images, and the reception of Thomasin's poem as well as into how it might be employed in present-day German language and literature classes. It proposes to replace the author-centered approach to the Welscher Gast with an approach that consistently focuses on the history of its transmission.